2018
DOI: 10.1038/s41467-018-06138-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the wheat Yr15 resistance gene sheds light on the plant tandem kinase-pseudokinase family

Abstract: Yellow rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a devastating fungal disease threatening much of global wheat production. Race-specific resistance (R)-genes are used to control rust diseases, but the rapid emergence of virulent Pst races has prompted the search for a more durable resistance. Here, we report the cloning of Yr15, a broad-spectrum R-gene derived from wild emmer wheat, which encodes a putative kinase-pseudokinase protein, designated as wheat tandem kinase 1, comprising a uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
235
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 252 publications
(258 citation statements)
references
References 63 publications
6
235
1
Order By: Relevance
“…The microscopic phenotype of Yr15 showed that the resistance response of this gene was distinct from other R genes and activated shorty after inoculation. This result supports the finding of the Yr15 cloning studies (Klymiuk et al , ). The cloning of Yr15 revealed that it encodes a putative kinase‐pseudokinase protein, designated as a wheat tandem kinase 1 (WTK1) belonging to the family of receptor‐like cytoplasmic kinases (RLCK) (Klymiuk et al , ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The microscopic phenotype of Yr15 showed that the resistance response of this gene was distinct from other R genes and activated shorty after inoculation. This result supports the finding of the Yr15 cloning studies (Klymiuk et al , ). The cloning of Yr15 revealed that it encodes a putative kinase‐pseudokinase protein, designated as a wheat tandem kinase 1 (WTK1) belonging to the family of receptor‐like cytoplasmic kinases (RLCK) (Klymiuk et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…This result supports the finding of the Yr15 cloning studies (Klymiuk et al , ). The cloning of Yr15 revealed that it encodes a putative kinase‐pseudokinase protein, designated as a wheat tandem kinase 1 (WTK1) belonging to the family of receptor‐like cytoplasmic kinases (RLCK) (Klymiuk et al , ). The decoy role, where host R protein mimics effector target to trap the pathogen, has been proposed as one of the potential mechanisms of function of RLCK family members in plant immunity (van der Hoorn & Kamoun, ).…”
Section: Discussionsupporting
confidence: 91%
“…So far, six WEW - derived Yr genes have been recognized ( Yr15, YrH52, Yr35, Yr36, YrTz2 , and YrSM139-1B ) on chromosome arms 1BS and 6BS (Huang et al , 2016a; Klymiuk et al , 2019a). Among these, only Yr36 (Fu et al , 2009) and Yr15 (Klymiuk et al , 2018) have been cloned so far.…”
Section: Introductionmentioning
confidence: 99%
“…Early surveys of the complete kinase domain complements from organisms including human, mouse, Caenorhabditis elegans , Dictyostelium and Arabidopsis found that pseudokinases like ZED1 account for ∼10% of the kinase domains in higher eukaryotes and 20% of Arabidopsis RLCKs [25,26]. Plant pseudokinases are emerging as important mediators of development and immunity [2729]. Rather than mere non-functional kinases resulting from relaxed (or absent) selective constraints, there is instead a growing body of evidence indicating that pseudokinases are important signaling molecules in spite of their predicted lack of catalytic activity, often functioning as adaptors or scaffolds that modulate the activity of true kinase partners [25,28,30,31].…”
Section: Introductionmentioning
confidence: 99%